Designs to balance cost and success rate for an early phase clinical study. Issue 1 (2nd January 2017) - Foo, Lee Kien; Duffull, Stephen
ABSTRACT: We present an initial exploration of a fully cost-driven design. A design criterion was proposed that represented the minimum expected cost of an early phase clinical study, where costs include resource use as well as study failure. The design was based on attainment of a target concentration in a cohort of study participants. The model and parameter values arose from a previous population pharmacokinetic analysis of a phase I study. The resulting design naturally balanced the cost and the success rate of an early phase clinical study, without the need to define arbitrary constraints on the design space.